CD8+ T lymphocytes protect SCID mice against Encephalitozoon cuniculi infection - Braunfuchsová, P; Salát, J; Kopecký, J (International journal for parasitology, 2001)
Microsporidia are obligate intracellular parasites that cause opportunistic infections in immunocompromised patients. The role of two main T cell subsets in anti-microsporidial immunity has been studied using an Encephalitozoon cuniculi-severe combined immunodeficient (SCID) mouse model. Whereas SCID mice reconstituted with CD4+ T lymphocyte-depleted naive BALB/c splenocytes resolved the infection, adoptive transfer of CD8+ T cell-depleted splenocytes failed to protect the animals against a lethal E. cuniculi infection. Splenocytes from E. cuniculi-immune mice specifically killed syngeneic infected macrophages in a short-term 51Cr-release assay. These results suggest the crucial role of cytotoxic T lymphocytes in the protection against E. cuniculi infection.
Keywords: Adoptive Transfer; Mice, Inbred BALB C; Mice, SCID; Cytotoxicity, Immunologic; Encephalitozoonosis; Mice; fenotyp; slezina; CD8-pozitivní T-lymfocyty; encephalitozoonóza; Phenotype; ženské pohlaví; zvířata; Encephalitozoon cuniculi; myši inbrední BALB C; myši; převzatá imunita; myši SCID; CD8-Positive T-Lymphocytes; Female; Spleen; cytotoxicita imunologická; Animals